Strengthening Capacities for Evidence-based Policy Planning and Implementation in Africa: IFPRI’s Support to CAADP in 2017–2018 - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Introduction: Since 2006, the International Food Policy Research Institute (IFPRI) has provided policy research and capacity-strengthening support to guide the planning and implementation of the Comprehensive Africa Agriculture Development Programme (CAADP). Endorsed in 2003 by African heads of state and government, CAADP is a continentwide framework for accelerating growth and progress toward poverty reduction and food and nutrition security through an agriculture-led growth strategy. As part of IFPRI’s support to CAADP, the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) was established in 2006 to provide policy-relevant analysis, data, and tools necessary to support the formulation and implementation of evidence-based agricultural-sector policies and strategies, as well as to facilitate CAADP policy dialogue, peer review, benchmarking, and mutual learning processes. ReSAKSS is facilitated by IFPRI in partnership with Africa-based CGIAR centers, the African Union Commission (AUC), the NEPAD Planning and Coordinating Agency (NPCA), and leading regional economic communities (RECs)